Genome Sequence of Verticillium dahliae Race 1 Isolate VdLs.16 From Lettuce - Jie-Yin Chen; Dan-Dan Zhang; Jin-Qun Huang; Dan Wang; Shi-Jun Hao; Ran Li; Krishna D. Puri; Lin Yang; Bang-Zhuo Tong; Ke-Xu Xiong; Ivan Simko; Steven J. Klosterman; et al. (Molecular Plant-Microbe Interactions, 2020)
Verticillium dahliae is a widespread fungal pathogen that causes Verticillium wilt on many economically important crops and ornamentals worldwide. Populations of V. dahliae have been divided into two distinct races based upon differential host responses in tomato and lettuce. Recently, the contemporary race 2 isolates were further divided into an additional race in tomato. Herein, we provide a high-quality reference genome for the race 1 strain VdLs.16 isolated from lettuce in California, U.S.A. This resource will contribute to ongoing research that aims to elucidate the genetic basis of V. dahliae pathogenicity and population genomic diversity.